The prevalence and characteristics of patients with ST-elevation myocardial infarction during the first two months of the COVID-19 pandemics. (14th October 2021) - Steinmetz, Y; Wolff, R; Farkash, R; Dadon, Z; Levi, N; Anguizola, F; Taha, L; Shaheen, F; Glikson, M; Asher, E; ,
Abstract: Background: ST-Segment elevation MI (STEMI) is one of the leading cause of mortality in the western world. The coronavirus disease-2019 (COVID-19) pandemic might have implications of the treatment of STEMI patients. Our aim was to evaluate the treatment of STEMI patients during 2 months of the COVID-19 pandemic as compared with the year before. Methods: Data of 90 STEMI patients treated at the Shaare Zedek Medical Center intensive coronary care unit (ICCU) Between March-April 2019 and March-April 2020 were collected. Patients were divided into 2 groups: The pre COVID-19 group and the COVID-19 era group. Data regarding complications upon arrival and during hospitalization, door to balloon time and echocardiographic exams. Results: Fifty one (56%) patients were admitted with STEMI in the pre COVID-19 group and only 39 (44%) in the COVID-19 era group. Of them 13.7% vs. 20.5% were female, p=0.392 with a mean age of 62.1 (±13.5) vs. 63.4 (±11) years old, p=0.635 in the pre vs. post COVID-19 era group, respectively. Interestingly, more Jewish vs. non-Jewish were admitted with STEMI in the COVID-19 era group. There were no differences regarding baseline characteristics, catheterization access, culprit vessel and percutaneous coronary intervention rate. Door to balloon time was also similar in both pre and post COVID-19 era groups 35.4 (±32) vs. 30.5 (±29.1) minutes (p=0.896). Moreover, there was no difference regarding infarct size. Complications including acute renal failure, cardiogenic shock, and the use of intra-aortic balloon pump were similar in both groups. 30-day mortality rate was low and similar in both pre and post COVID-19 era groups (5.9% vs. 2.6%, respectively, p=0.426). Conclusions: During the beginning of COVID-19 era there was a reduction in STEMI admission rate, while no significant difference was found regarding baseline characteristics, door to balloon time, infarct size and mortality rate FUNDunding Acknowledgement: Type of funding sources: None.